Variation of Particle Pretreatment on Termites Attack of Particleboard Made from Waste Oil Palm Trunks using Urea Formaldehida Resin - Kaya Muda Lubis; Rudi Hartono; Tito Sucipto; Apri Heri Iswanto (Peronema Forestry Science Journal, 2014)
The waste of oil palm trunk could be used as alternative raw material for particleboard. The purpose of these studies were to evaluate durability of particleboard on termites attack. Particle pretreatment were done by hot water soaking (1 hour, 2 hours, 3 hours) and cold water soaking (24 hours, 48 hours, 72 hours). Particle board were made from waste of oil pulm trunk using urea formaldehida of 10% with size 30 cm x 30 cm x 1 cm, density target 0.75 g/cm3, pressure 25 kg/cm2 at 130ºC of temperature for 10 minutes. Particleboard was tested for durability of particleboard on termites attack by grave yard test along 100 days and wil be compared by SNI 01-7207-2006.The percentages of particleboard weight loss were 41.05-60.29%. Based on the termites attack rate, all of particleboards were classified as very bad durability. The best of particleboards durability was the board with cold water soaking for 72 hours treatment with 41.05% of particleboard weight loss.Keywords : oil palm trunk, urea formaldehida, particle pretreatment, particle board, subterranean termites.